CORRELATIONS BETWEEN SYSTEMIC THERAPY WITH CONVENTIONAL (SYNTHETIC) AND BIOLOGICAL DMARDS, RHEUMATOID ARTHRITIS AND PERIODONTAL INDICES OF CHRONIC PERIODONTITIS - Maria Alexandra Martu; Elena Rezus; Cristina Popa; Sorina Mihaela Solomon; Ionut Luchian; Arina Ciocan Pendefunda; Ioana Sioustis; Diana Anton; Silvia Martu; Liliana Foia (Romanian Society of Oral Rehabilitation, 2019)
The purpose of the study. This study proposes an analysis of local inflammatory status by evaluating Quigley Hein indices, papillary bleeding indices (PBI) and gingival Lõe and Silness indices, accompanied by a detailed assessment of systemic status (VSH, CRP) in patients with rheumatoid arthritis and synthetic and biological DMARDs therapy. Results and discussions. DMARDs determine the level of CRP and FR markers, the rate of erythrocyte sedimentation, and cartilage and bone damage. In the present study, serum levels of VSH and CRP recorded individual values higher than the maximum reference limit for 48.2% and respectively 46.3% of the patients, the mean level being significantly higher in the advanced stages of the disease. Measurement of oral markers revealed the the lowest average level of Quigley Hein score in patients treated with Sulfasalazine + Rituximab, while the highest values were recorded for Leflunomide + Etanercept therapy. The lowest average level for GI score was seen in patients treated with Methotrexate + Adalimumab and Leflunomide + Adalimumab, and the largest was found in patients treated with Leflunomide + Rituximab and Methotrexate + Rituximab. Regarding the treatment of RA, we could not establish a clear effect on oral health ratios of conventional and synthetic DMARDs combined therapy. However, it is important to note that, in contrast, in patients receiving biological DMARDs treatment, the average level of oral health indices was significantly lower. Thus, we can note the positive influence that this class of drugs, especially those that act on TNF-α, generates it on local status. Conclusions. To maintain oral health, patients with AR are encouraged to achieve proper oral hygiene. Consultation of the periodontist is necessary to determine the course of treatment.